Energy Demand Challenges in Europe Implications for policy, planning and practice - Fahy, Frances; Goggins, Gary; Jensen, Charlotte (Springer Nature, 2019)
This open access book examines the role of citizens in sustainable energy transitions across Europe. It explores energy problem framing, policy approaches and practical responses to the challenge of securing clean, affordable and sustainable energy for all citizens, focusing on households as the main unit of analysis. The book revolves around ten contributions that each summarise national trends, socio-material characteristics, and policy responses to contemporary energy issues affecting householders in different countries, and provides good practice examples for designing and implementing sustainable energy initiatives. Prominent concerns include reducing carbon emissions, energy poverty, sustainable consumption, governance, practices, innovations and sustainable lifestyles. The opening and closing contributions consider European level energy policy, dominant and alternative problem framings and similarities and differences between European countries in relation to reducing household energy use. Overall, the book is a valuable resource for researchers, policy-makers, practitioners and others interested in sustainable energy perspectives.